COMMUNICATION-BASED CLASSROOMS: A NEW APPROACH TO INCLUSIVE EDUCATION - Muhammad Yazidus Syukri; Erna Widyasari; Djalal Fuadi (CV. ADIBA AISHA AMIRA, 2024)
Communication-based classrooms are an inclusive education approach that utilises augmentative and alternative communication (AAC) technologies to support learners with special needs. The aim is to increase learners' participation, engagement and communication skills in the learning process, as well as to address their communication barriers. It also aims to develop digital literacy and social integration skills, creating a more inclusive and supportive learning environment. The study in this research uses the literature study method. The results show that: firstly, communication-based classrooms have benefits for improving learners' digital literacy skills, better social integration and emotional well-being. Secondly, this method can help overcome communication barriers often experienced by learners with special needs, giving them equal opportunities to reach their academic and social potential. Thirdly, there are challenges in implementing communication-based classrooms such as limited resources and budgets, lack of teacher training and skills, difficulties in integration with the current curriculum, and mixed attitudes and acceptance from learners, teachers and parents towards the use of technology in education. Overcoming these challenges requires a holistic approach that includes increased budgets, continuous training for teachers and socialisation to change negative views about technology in education